End of story?: same-sex relationships and the narratives of evangelical mission - Perriman, Andrew (Cascade Books, 2019)
This book is an exercise in a thoroughgoing narrative theology. The social and legal validation of same-sex relationships in the West over the last two decades has presented an immense challenge to the church insofar as it seeks to remain faithful to Scripture. But it is not an isolated ethical problem. It is just one element--albeit a very important one--in the much broader, long-term overhaul and reorientation of Western culture after the collapse of the Christian consensus. The forces of history that are driving this transformation, however, have also alerted us to the historical perspectives that constrained biblical thought. Andrew Perriman suggests that Paul's argument about same-sex behavior, perhaps more clearly than any other issue, highlights the narrative shape of the mission of the early church in the Greek world. By the same token, we must ask how that storyline has been refracted across the boundary of modernity, and how it now shapes the mission of the church as it adapts to its marginalized position in an aggressively secular world